A case of tuberculous peritonitis in childhood. Issue 4 (July 2015) - Avcu, Gulhadiye; Sensoy, Gulnar; Karli, Arzu; Caltepe, Gonul; Sullu, Yurdanur; Belet, Nursen; Bilgici, Meltem C.
Summary Currently, tuberculosis remains a major public health problem worldwide. Peritoneal tuberculosis occurs in approximately 1% of all of tuberculosis cases and is rarely observed in children. Diagnosis and treatment delays caused by mimicking many other intra-abdominal diseases can lead to increases in morbidity and mortality. Here, we present a case of a four-year-old child with tuberculosis peritonitis who was diagnosed by laparoscopic biopsy and histopathological examination and recovered with antituberculosis therapy. Peritoneal tuberculosis should be considered in younger patients and adults with fever, abdominal pain and weight loss in endemic areas.